Heterotrimeric G Protein α-Subunits - Structures, Peptide-Derived Inhibitors, and Mechanisms - Voss, Jan H.; Müller, Christa E. (Current Medicinal Chemistry, 2022)
G protein-coupled receptors are the largest protein family in the human body and represent the most important class of drug targets. They receive extracellular signals and transduce them into the cytosol. The guanine nucleotide-binding Gα proteins represent the main relays by which GPCRs induce intracellular effects. More than 800 different GPCRs interact with 16 Gα proteins belonging to 4 families, Gαi, Gαs, Gαq, and Gα12/13. The direct inhibition of Gα protein subunits rather than the modulation of GPCR subtypes has been proposed as a novel strategy for the treatment of complex diseases, including inflammation and cancer. This mini-review presents an introduction to G protein structure and function and describes achievements in the development of peptidic and peptide-derived Gα protein inhibitors. They have become indispensable pharmacological tools, and some of them exhibit significant potential as future drugs.
Keywords: peptide